간호사의 디지털 헬스 리터러시, 디지털 헬스 활용도 현황 및 관련 요인 - 신지은(Ji-Eun Sin); 박종욱(Jong-Uk Park); 김남이(Nam-Yi Kim) (보건교육건강증진학회지, 2023)
Objectives: This study aimed to investigate the current status of nurses’ digital health literacy and digital health utilization and to identify related factors as basic data for their improvement. Method: An online survey of 154 nurses was conducted from November 1 to 30, 2022. Independent t-tests and one-way ANOVA were conducted to analyze the difference in digital health literacy and digital health utilization by respondents’ general characteristics and health characteristics. Multiple regression analysis was then conducted on the relevant factors. Results: Nurses’ digital health literacy was positively correlated with digital health utilization. With regard to nurses’ digital health utilization, information search and individual subjective health awareness were the main influencing factors among digital health literacy. Conclusion: In order to improve nurses’ subjective health awareness, education and programs related to personal health behaviors should be implemented. Training using various digital health devices and systems is needed to improve information retrieval capabilities. KCI Citation Count: 0